A new scoring system and clinical algorithm for the management of suspected foreign body aspiration in children: a retrospective cohort study - Nader A. Fasseeh; Osama A. Elagamy; Alaa H. Gaafar; Heba M. Reyad; Mohamed S. Abougabal; Doaa A. Heiba; Ahmad Kantar (BMC, 2021)
Abstract Background Cases of foreign body aspiration in children may be encountered in emergency departments. A suggestive history is important in diagnosing aspirated foreign body owing to the difficulty in making a diagnosis on the basis of an abnormal physical examination or chest radiography alone. The aim of this study was to examine the sensitivity and specificity of the presenting symptoms, physical examination, and radiologic findings as predictors of foreign body aspiration in children. In addition, a feasible simple algorithm with a scoring system was generated to indicate bronchoscopic investigation. Methods In a retrospective cohort, medical records of patients aged less than 16 years with suspected foreign body aspiration who underwent flexible or rigid bronchoscopy were included. Data including age, sex, symptoms, physical examination findings, radiological features, nature and location of the foreign body, and outcome of the bronchoscopy were collected, and multivariable binary logistic regression analysis was employed for prediction of foreign body aspiration. Results A total of 203 children were included, and the model showed excellent discrimination power for positive foreign body aspiration (area under the curve = 0.911) with an accuracy, sensitivity, and specificity of 86.2, 90.6, and 76.6%, respectively. The total weighted risk score at a cut-off > 2 showed a significant good power of discrimination (area under the curve = 0.879), with a sensitivity of 79.9% and specificity of 84.4%. Accordingly, a clinical algorithm was recommended. Conclusions The proposed scoring system and clinical algorithm might help in decision making with regard to the need and type of bronchoscopy in children presenting with potential foreign body aspiration. However, further prospective multicenter studies should be conducted to validate this scoring system.